Genome-Wide Identification of Wild Soybean Mitochondrial Calcium Uniporter Family Genes and Their Responses to Cold and Carbonate Alkaline Stresses - Li, Jianwei; Sun, Mingzhe; Liu, Yu; Sun, Xiaoli; Yin, Kuide (Frontiers in Plant Science, 2022)
The mitochondrial calcium uniporter (MCU), as an important component of the Ca2+ channel uniporter complex, plays a regulatory role in intracellular Ca2+ signal transduction. However, only a few studies to date have investigated plant MCU genes. In this study, we identified the MCU family genes in wild soybean and investigated their expression under cold and carbonate alkaline stresses. Eleven Glycine soja MCU genes (GsMCUs) were identified and clustered into two subgroups (subgroups I and II), and subgroup II could be further divided into two branches (MCU5 and MCU6). A total of 21 pairs of GsMCUs were characterized as duplicated genes, and displayed a similar exon-intron architecture. All GsMCU proteins contained one conserved MCU domain, within which two transmembrane domains were found. An analysis of the conserved motifs further supported that the GsMCUs showed high conservation in protein sequence and structure. Moreover, we found that all GsMCUs were expressed ubiquitously in different tissues and organs, and GsMCUs from the same subgroup displayed varied tissue expression profiles. In addition, based on RNA-seq and qRT-PCR assays, six and nine GsMCUs were differentially expressed under cold and carbonate alkaline stress, respectively. Promoter analysis also uncovered the existence of two canonical cold-related cis-acting elements, LTR and DRE/CRT, as well as stress-related phytohormone-responsive elements. Our results provide valuable information about the MCU family in soybean responses to cold and carbonate alkaline stress, which will be helpful in further characterizing their biological roles in response to abiotic stress.